2004
DOI: 10.1063/1.1783592
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent electron tunneling through time-dependent tunnel barriers

Abstract: A plane electron wave incident on a tunnel-transparent potential barrier formed by the potential V͑x , t͒ = V 0 ͑x͒ + V 1 ͑x͒cos t generates, in addition to the usual stationary transmitted and reflected stationary waves, also "transmitted" and "reflected" electron waves oscillating with the same frequency. The transmitted oscillating wave can serve as the basis for transit-time microwave generators oscillating in the terahertz range. (Such oscillators are ballistic analogs of the tunnel-emission transit-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…Another important feature shared by all such types of CTRW is that if one is only interested in the average survival amplitude (or Weyl differential) of the initial eigenstate |k 0 then as we have seen from Fig.1(c,d), Eqs. (15) are in excellent agreement with the numerics for each realization. Therefore one can average these formulae directly and arrive at the following amazing statement: Regardless of the nature of the symmetric CTRW of a narrow potential barrier the average survival amplitude f (k 0 , t) of an eigenstate |k 0 is just the characteristic function Φ(k 0 , t) of the current position of the scatterer γ(t).…”
Section: The Disorder-averaged Quantum Propagatorssupporting
confidence: 80%
“…Another important feature shared by all such types of CTRW is that if one is only interested in the average survival amplitude (or Weyl differential) of the initial eigenstate |k 0 then as we have seen from Fig.1(c,d), Eqs. (15) are in excellent agreement with the numerics for each realization. Therefore one can average these formulae directly and arrive at the following amazing statement: Regardless of the nature of the symmetric CTRW of a narrow potential barrier the average survival amplitude f (k 0 , t) of an eigenstate |k 0 is just the characteristic function Φ(k 0 , t) of the current position of the scatterer γ(t).…”
Section: The Disorder-averaged Quantum Propagatorssupporting
confidence: 80%
“…1 In the case of the rectangular barrier with a time-dependent height B = 0 + ͑1͒ cos t, the formula, which is analogous to Eq. We can hope that the optimal working regime for the high-frequency tunnel emitters can be realized if ͑A /2Qw͒exp Qw Ϸ 1 or ͓eE B ͑␦ − ͒ / gប͔exp͓បgw /2͑␦ − ͔͒ Ϸ 1.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous article, 1 we considered several models relating to a time-dependent electron tunneling through nonstationary tunnel emitter barriers. As is known, 2-5 the quasistatic approach based on the use of the static tunneling equations becomes incorrect if a characteristic frequency tends to the terahertz range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The part left back evolves within the modulated barrier and part of it tunnels across the periodically modulated barrier [5]. Typically for a barrier modulated at a frequency , the solutions for the reflected and transmitted waves not only have the usual stationary wave solution, but also have waves which are reflected and transmitted at frequency  [2,5,6,7]. It has also been suggested that under certain conditions, a continuous drive may lead to localization and completely destroy coherent tunneling across the barrier [8,9,10].…”
Section: Introductionmentioning
confidence: 99%